Pengaruh Stress Kerja dan Kompensasi Terhadap Turnover Intention Karyawan pada PT Telkom Indonesia Cabang Bima - Sukran Sukran; Mulyadin Mulyadin (Journal of Business and Economics Research (JBE), 2020)
This study aims was to determine the effect of job stress (X1) and compensation (X2) on employee turnover intention (Y) on PT. Telkom Indonesia branch Bima. The method used in this research is a qualitative method, with the type of associative research. The sampling technique used is the Probability Sampling technique, the number of samples used was 54 respondents from a total of 119 employees and used the Slovin formula. The sampling method using simple random sampling. Based on the results of the analysis of this study, it shows that work stress (X1) and compensation (X2) have a simultaneous effect on employee turnover intention (Y).